Sistematik Review: Dampak Perkuliahan Daring Saat Pandemi COVID-19 Terhadap Mahasiswa Indonesia - Niken Bayu Argaheni (PLACENTUM: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2020)
Background: Learning online and working from home for educators is a change that must be made by lecturers to continue teaching students. Distance education has the aim of improving the quality of education and the relevance of education as well as increasing the equitable access and expansion of education. Distance Education that is carried out with good quality assurance and in accordance with the needs of stakeholders is one mechanism for expanding access to quality higher education that is expected.Method: Systematic review using a database: Google Scholar. Search results that fulfill the criteria are then analyzed by article.Results: Online learning has several impacts on students, namely (1) Online Learning Still Confuses Students (2) Students become passive, less creative and productive, (3) The accumulation of information / concepts on students is less useful, (4) Students Experiencing Stress, (5) Improvement of Student Language Literacy Ability.Conclusion: At present, the spread of Covid-19 still shows an upward trend so that education practitioners and stakeholders can continue to survive and innovate in implementing learning. This is because good learning is able to invite students' interest and attention.